The traditional trade at the city that products itself: Belo Horizonte’s downtown - Freire, Ana Lucy Oliveira (GEOUSP Espaço e Tempo (Online), 1998)
This article discu sses the transform ations suffered by the traditional trade located at Belo Horizonte's downtown area. First we analise the effects of the consumption, that goes far beyond the minimun required for a human being survive, on the urban space production. Then, we discuss the concepts of "downtonw area" and of "trade" trying to make a connection between them . Finally, we see how works the Belo Horizonte's downtown area traditional trade, its characteristics and its im portance to the city